Means against the rule of nobody - Mirko Pečarič (DANUBE: Law, Economics and Social Issues Review, 2018)
This paper presents means by which relations between facts and decisions can be put on a higher, more transparent and accountable level. The complexity of relations, their exponential effects, new technology and numerous rules have increased the public administration's unaccountability for its actions - if it is even possible to talk about accountability at all. This kind of situation is presented as the rule of nobody that through multiple relations, competencies and division of labour diminishes the possibility to view a situation as a whole, and enhances the distinction between a person's formal role and his inner personal world. Classical decision-making procedures (more or less still) exclude interactions between political-legal and scientific institutions on one side and between the first and social groups on the other about modern risks that go beyond classical factory-related or occupational hazards. If the presented means (performance indicators, the avoidance of exclusive subjective evidence, the use of probability in individual cases, the right to clear information, the office for legislation and regulatory analysis and an IT platform) were formally integrated into decision-making, they could enable democratisation, for which the non-stop present and available communication links are sine qua non.
Keywords: 330; Rule of Nobody; Evidence-Based Regulation; Performance Indicators; Probability; Right to Clear Information